Patient engagement in cosmetic designing of prostheses: current practice and potential outcome benefits. Issue 4 (22nd August 2022) - Lee, Szu-Ping; Mitchell, Cailin; Repayo, Kenneth; Tillitt, Matthew; Weber, Collin; Chien, Lung-Chang; Doerger, Chris
Abstract : Background: Making a prosthesis for an individual with limb loss is a highly personalized process. A currently unexplored area is whether there are tangible benefits in greater patient engagement during the cosmetic designing of their prostheses. We examined the current clinical practice of engaging patients in prosthetic cosmetic designing and identified factors associated with patient outcomes. Methods: One hundred and four prosthetists and 28 prosthesis users were surveyed in this cross-sectional study. The questionnaires covered aspects of prosthetic prescription and fabrication, users' perceived level of engagement, and self-reported outcomes. Regression analyses were used to examine the associations between patients' perceived levels of engagement during the design process, satisfaction, and other outcomes. Results: Seventy-five percent of the prosthesis users reported being offered at least one cosmetic option during the making of their prostheses, which corroborated with 82.7% of the prosthetists reporting that they typically engage their patients in this aspect of their practices. Patients who were offered at least one cosmetic design option reported significantly greater satisfaction ( P = 0.027) than those who were not offered such an option. Patients' level of satisfaction regarding the look of their prostheses was significantly correlated with their perception that their prostheses empower them in daily activities (r = 0.415, P = 0.028). Conclusion: Engaging patients in the cosmetic designing of their prostheses is a widely accepted practice. Patients who are more satisfied with the look of their prostheses perceived higher levels of empowerment. Prosthetic practitioners should consider the potential outcome benefits of higher level engagement for users of prosthetic devices.